Digital human resources management: a necessity in modern organizations - Hajar, Siti (Trigin Publisher, 2024)
This paper will discuss a simple overview of how the concept of human resource management is carried out with digitalization. The explanation will be based on various existing studies, so that an elaborate and comprehensive picture of the new paradigm of human resource management based on the power of digital computing technology can be given. This research model tries with all its might to elaborate various scientific sources that will strongly support the construction of the analysis of a particular study. This research method is a qualitative research method with a descriptive approach. This research operationally examines various sources of literature relevant to the context of the above research. Digital Human Resource Management is considered as the basic need in the aspect of business organization. Every business organization has a long way to go by adopting digitalization. Digital HRM helps in maintaining a strong relationship between management and its employees. By preparing a strategy for DHRM will help in organizational performance.